PERAN CONCRETE-PICTORIAL-ABSTRACT (CPA) APPROACH DAN STUCTURED PROBLEM SOLVING DALAM PEMBELAJARAN MATEMATIKA DI SD/MI - Nuryana, Eti; Fiteriani, Ida; Afriyadi, Muhammad Muchsin (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This research is motivated by the low mathematical literacy and problem-solving abilities of elementary school students, which are still influenced by conventional learning and students' difficulties in understanding abstract mathematical concepts. This study aims to analyze the role of the Concrete-Pictorial-Abstract (CPA) Approach and Structured Problem Solving (SPS) in mathematics learning in elementary school students through the Systematic Literature Review (SLR) method. The research was conducted by referring to the PRISMA 2020 guidelines through the stages of identification, screening, eligibility, and inclusion. Data sources were obtained from the Scopus, ERIC, and ScienceDirect databases in the period 2020–2025. Of the 799 articles found, 12 articles met the inclusion criteria and were analyzed descriptively qualitatively. The results showed that CPA effectively improved students' conceptual understanding, numeracy, mathematical reasoning, and learning motivation through concrete, pictorial, and abstract stages. Meanwhile, SPS effectively improved problem-solving skills, logical, critical, and systematic thinking through Polya-based problem-solving steps. The integration of CPA and SPS is considered capable of creating more meaningful, systematic mathematics learning that aligns with the cognitive developmental characteristics of elementary school students.